2018
DOI: 10.1111/clr.13257
|View full text |Cite
|
Sign up to set email alerts
|

Injectable, compression‐resistant polymer/ceramic composite bone grafts promote lateral ridge augmentation without protective mesh in a canine model

Abstract: At the same dose of rhBMP-2, an injectable, compression-resistant bone graft resulted in a comparable volume of new bone formation with the clinical control (ACS). These findings highlight the potential of compression-resistant bone grafts without the use of protective mesh for lateral ridge augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…These evidence the process of biodegradation of the implant and suggest adequate biocompatibility of the material. The use of bioceramics tends to promote a more discreet bone neoformation, which may explain the discrete periosteal reaction observed in a single animal in the present study (Talley et al, 2018).…”
Section: Radiographs Of the Scaffolds After Implantationmentioning
confidence: 58%
“…These evidence the process of biodegradation of the implant and suggest adequate biocompatibility of the material. The use of bioceramics tends to promote a more discreet bone neoformation, which may explain the discrete periosteal reaction observed in a single animal in the present study (Talley et al, 2018).…”
Section: Radiographs Of the Scaffolds After Implantationmentioning
confidence: 58%
“…PUR foams augmented with recombinant human bone morphogenetic protein (rhBMP-2) have been reported to support the regeneration of bone tissue (34,35). While these foams degrade after 8 to 16 weeks in vivo (36,37), our results suggest that even resorbable drug delivery platforms such as PUR foams can harbor significant numbers of bacteria during acute infection. Antibiotic-loaded PUR foams have been shown to decrease bacterial burdens (7,26); however, tuning the release kinetics to deliver an effective dose for a sustained time period remains a major limitation.…”
Section: Discussionmentioning
confidence: 68%
“…Lysine-based poly(ester urethanes) (PEURs) and poly(thioketal urethanes) (PTKURs) have been previously investigated in bone regeneration applications [ 30 , 31 , 32 , 33 ]. The mechanical properties of these materials can be easily altered, and the addition of ceramic particles, AG, and allograft supports new bone formation at various anatomic sites [ 34 , 35 , 36 , 37 ]. Previous work has demonstrated selective, cell-mediated, first-order degradation of PTKUR in vivo [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Slow degradation is advantageous in applications in which mechanical stability is required; however, in applications utilizing biologics, faster graft resorption is necessary to harness the osteoinductivity. In a previous study, PEUR was used to deliver rhBMP-2 and demonstrated balanced polymer resorption and new bone formation [ 34 , 40 ]. Therefore, we compared PEUR [ 41 , 42 ] with PTKUR [ 38 ] as an AG extender to test the hypothesis that faster degrading PEUR would support increased cellular infiltration and bone formation in a rabbit radius model.…”
Section: Introductionmentioning
confidence: 99%